AtMYB44 regulates WRKY70 expression and modulates antagonistic interaction between salicylic acid and jasmonic acid signaling. (10th December 2012) - Shim, Jae Sung; Jung, Choonkyun; Lee, Sangjoon; Min, Kyunghun; Lee, Yin‐Won; Choi, Yeonhee; Lee, Jong Seob; Song, Jong Tae; Kim, Ju‐Kon; Choi, Yang Do
Summary The role of AtMYB44, an R2R3 MYB transcription factor, in signaling mediated by jasmonic acid (JA) and salicylic acid (SA) is examined. AtMYB44 is induced by JA through CORONATINE INSENSITIVE 1 (COI1). AtMYB44 over‐expression down‐regulated defense responses against the necrotrophic pathogen Alternaria brassicicola, but up‐regulated WRKY70 and PR genes, leading to enhanced resistance to the biotrophic pathogen Pseudomonas syringae pv. tomato DC3000. The knockout mutant atmyb44 shows opposite effects. Induction of WRKY70 by SA is reduced in atmyb44 and npr1‐1 mutants, and is totally abolished in atmyb44 npr1‐1 double mutants, showing that WRKY70 is regulated independently through both NPR1 and AtMYB44. AtMYB44 over‐expression does not change SA content, but AtMYB44 over‐expression phenotypes, such as retarded growth, up‐regulated PR1 and down‐regulated PDF1.2 are reversed by SA depletion. The wrky70 mutation suppressed AtMYB44 over‐expression phenotypes, including up‐regulation of PR1 expression and down‐regulation of PDF1.2 expression. β‐estradiol‐induced expression of AtMYB44 led to WRKY70 activation and thus PR1 activation. AtMYB44 binds to the WRKY70 promoter region, indicating that AtMYB44 acts as a transcriptional activator of WRKY70 by directly binding to a conserved sequence element in the WRKY70 promoter. These results demonstrate that AtMYB44 modulates antagonistic interaction by activating SA‐mediated defenses and repressing JA‐mediated defenses through direct control of WRKY70.